Analysis of the Relationship Between Renewable Energy and Economic Growth in Selected Developing Countries - Syzdykova, Aziza; Abubakirova, Aktolkin; Erdal, Fehmi Bugra; Saparova, Ainura; Zhetibayev, Zhanture (International Journal of Energy Economics and Policy, 2020)
Whether there is a relationship between economic growth and energy consumption and the direction of this relationship is of great importance in energy policy decision making in countries where the state plays an active role in energy markets. If there is a relationship from energy to growth, conservative policies such as energy taxes, energy-saving, and energy prices will hurt growth. There are many studies in the literature investigating the effects of renewable and non-renewable energy consumption on the economic growth of countries. Since different data, periods, and methods were used in the studies, consensus could not be achieved. Therefore, this issue remains current and continues to be investigated. The main purpose of this study is to determine whether renewable energy consumption has a positive effect on economic growth for selected developing countries (Brazil, India, Indonesia, China, Chile, Mexico, South Africa and Turkey). Fossil energy consumption and CO2 emissions variables are also included in the model established for this purpose. GMM estimator, one of the dynamic panel data methods, was used for empirical analysis of the relationship between these variables. Keywords: renewable energy consumption, carbon emission, economic growth, Dynamic panel data, GMM method JEL Classifications: O40, Q43, Q40 DOI: https://doi.org/10.32479/ijeep.10397